Optimization of Lipase-Catalysed Synthesis and Characterization of Kojic Acid Esters - Khamaruddin, Noor Hayati (2007)
Kojic acid ester was successfully synthesized by esterification using lipase from Pseudomanas cepacia (Amano PS) as a biocatalyst in an organic media. The reaction mixture consisted of 90 mM of oleic acid, 360 mM of kojic acid and 0.15 g Amano PS in the presence of 2 mL of acetonitrile. The mixture was incubated at temperature of 50°C for 24 hour at shaking speed of 150 rpm. Lipozyme IM, Novozym 435, Pseudomonas cepacia lipase, Aspergillus niger, Candida rugosa and Eupergit C-Lipase were tested for their suitability as the enzyme in the reaction. Among the enzymes tested, lipase from Pseudomonas cepacia gave the highest enzyme activity (0.015 yield/μg protein content) and specific activity (3.738 x 10-6 mmol ester/min/mg protein content) in the synthesis. Oleic acid was found to be the best substrate to produce the ester but must be in the presence of acetonitrile as an organic solvent. The maximum percentage yield using Pseudomonas cepacia lipase at optimal condition was 44% without removal of water from the reaction mixture. From the optimization studies, kojic acid derivatives can be synthesized from palm oil and kojic acid, by Pseudomonas cepacia lipase (Amano PS). TLC analysis showed that kojic acid ester gave an Rf value of 0.28 in the TLC plate and a retention time of 31.752 min in the gas chromatogram. The product formation and the reactant disappearance were monitored by IR spectroscopy. A strong C=O stretching of the ester at 1746 cm-1 and weak absorption peak of O-H in the unreacted kojic acid indicated completion of the esterification reaction. The gas chromatography-mass spectrometry (GC-MS) analysis gave a molecular ion peak at m/z 478 which was due to the kojic acid ester. 1H-NMR and 13C-NMR spectral data confirmed the molecular structure of the kojic acid ester.